2010
DOI: 10.1577/t09-225.1
|View full text |Cite
|
Sign up to set email alerts
|

Unintended Effects of Electrofishing on Nongame Fishes

Abstract: Most studies of injury associated with electrofishing have focused on game fishes, but few have given attention to cohabiting small nongame species. Under controlled laboratory conditions, we subjected small nongame cyprinids, ictalurids, and percids to a wide range of voltages and waveforms to examine potential harmful effects. Fish were treated with power levels distributed uniformly between the thresholds required to immobilize game fish and also were subjected multiple times to those thresholds to simulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 19 publications
2
23
0
Order By: Relevance
“…This accords with previous experiments in which fish was exposed below immobilization threshold (Dolan and Miranda, 2003), but differs from studies in which fish, forced into cramp, were often found with mortality rates ranging from 0 to 30% (De Haan et al, 2009b;Dolan et al, 2002;Dolan and Miranda, 2004;Schreer et al, 2004;Sharber and Carothers, 1988;Sharber et al, 1994). However, as the rates of mortality and injuries are not always directly related (Dalbey and Mc Mahon, 1996;Dolan et al, 2002;Dolan and Miranda, 2004;Miranda and Kidwell, 2010), the exposed animals were further examined for external and internal as well as macroscopic and microscopic injuries.…”
Section: Injuriessupporting
confidence: 83%
“…This accords with previous experiments in which fish was exposed below immobilization threshold (Dolan and Miranda, 2003), but differs from studies in which fish, forced into cramp, were often found with mortality rates ranging from 0 to 30% (De Haan et al, 2009b;Dolan et al, 2002;Dolan and Miranda, 2004;Schreer et al, 2004;Sharber and Carothers, 1988;Sharber et al, 1994). However, as the rates of mortality and injuries are not always directly related (Dalbey and Mc Mahon, 1996;Dolan et al, 2002;Dolan and Miranda, 2004;Miranda and Kidwell, 2010), the exposed animals were further examined for external and internal as well as macroscopic and microscopic injuries.…”
Section: Injuriessupporting
confidence: 83%
“…Crappies showed spinal injuries at 5, 60 and 110 Hz but haemorrhaging was higher at 60 and 110 Hz, and mortality was only seen at 5 Hz (Dolan 2002). This was confirmed by Miranda and Kidwell (2010), who concluded that the mortality of the warm freshwater non-game test species was not related to gross-scale injuries because similar or worse haemorrhages and spinal injury were seen in fish that survived electroshock and those that died. This finding suggests that the mechanisms causing physical injuries are not the same as the mechanisms that cause immediate mortality.…”
Section: Harmful Effects On Freshwater Fish Speciesmentioning
confidence: 80%
“…Electrofishing is one of the most common methods for ecological monitoring in wadeable streams, but is occasionally avoided due to increased potential for mortality of threatened and endangered species (Henry, Grizzle, Johnston, & Osborne, ; Miranda & Kidwell, ). Electrofishing was generally the most efficient gear for detecting madtoms similar to related research (Poos, Mandrak, & McLaughlin, ; Pygott, O'Hara, Cragg‐Hine, & Newton, ; Wiley & Tsai, ), but like each other gear type, generally represented fish size structure poorly.…”
Section: Discussionmentioning
confidence: 99%